2014
DOI: 10.1158/1940-6207.capr-14-0108
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating Mutation in the Prostaglandin Transporter Gene, SLCO2A1, Associated with Familial Digital Clubbing, Colon Neoplasia, and NSAID Resistance

Abstract: HPGD and SLCO2A1 genes encode components of the prostaglandin catabolic pathway, HPGD encoding the degradative enzyme 15-PGDH, and SLCO2A1 encoding the prostaglandin transporter PGT that brings substrate to 15-PGDH. HPGD null mice show increased PGE2, marked susceptibility to developing colon tumors, and resistance to colon tumor prevention by NSAIDs. But in humans, HPGD and SLCO2A1 mutations have only been associated with familial digital clubbing. We here characterize a family with digital clubbing and early… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The SLCO2A1 translational initiation codon mutation (p.M1V) reported here causes recessive ICNC with no abnormal phenotype in heterozygotes. In contrast, a heterozygous SLCO2A1 nonsense mutation (p.G104X) was reported in a family with autosomal dominant ICNC, colon neoplasia and non‐steroidal anti‐inflammatory drug resistance . A different heterozygous SLCO2A1 nonsense mutation (p.R252X) has been reported in a patient with sporadic ICNC, in an unaffected relative and also in patients with PDP .…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The SLCO2A1 translational initiation codon mutation (p.M1V) reported here causes recessive ICNC with no abnormal phenotype in heterozygotes. In contrast, a heterozygous SLCO2A1 nonsense mutation (p.G104X) was reported in a family with autosomal dominant ICNC, colon neoplasia and non‐steroidal anti‐inflammatory drug resistance . A different heterozygous SLCO2A1 nonsense mutation (p.R252X) has been reported in a patient with sporadic ICNC, in an unaffected relative and also in patients with PDP .…”
mentioning
confidence: 56%
“…Similarly, various loss‐of‐function and missense mutations in SLCO2A1 have also been reported both in families with autosomal recessive PHO and PDP . In addition, heterozygous SLCO2A1 loss‐of‐function mutations have been reported in a family with autosomal dominant ICNC and in a case of sporadic ICNC …”
mentioning
confidence: 99%
“…Observational data have already suggested that the benefit of aspirin may be dependent upon mutations in PIK3CA in individuals with a diagnosis of colon cancer; and familial data suggests that a mutation in SLCO2A1 , a member of the prostaglandin catabolic pathway, is associated with early colonic neoplasia and NSAID resistance. 119, 120 …”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…Because the skewed sex ratio and typical puberty onset are not observed in PHOAR1, it suggests a key role of sex hormones in PGT regulation. Additionally, previous studies scatteredly indicated the potential differences with respect to the clinical spectrum between PHOAR1 and PHOAR2 . However, systematic analyses were absent.…”
Section: Introductionmentioning
confidence: 98%